Perceived warmth and competence of others shape voluntary deceptive behaviour in a morally relevant setting. - Azevedo, Ruben T.; Panasiti, Maria Serena; Maglio, Rosita; Aglioti, Salvatore Maria (British Journal of Psychology, 2018)
The temptation to deceive others compares to a moral dilemma: it involves a conflict between the temptation to obtain some benefit and the desire to conform to personal and social moral norms or avoid aversive social consequences. Thus, people might feel different levels of emotional and moral conflict depending on the target of the deception. Here we explored, in a morally relevant setting, how social judgements based on two fundamental dimensions of human social cognition - 'warmth' and 'competence' - impact on the decision to deceive others. Results revealed independent effects for warmth and competence. Specifically, while people are less inclined to deceive for self-gain those individuals they perceive as warm, they also tend to lie more to highly competent others. Furthermore, the perceived warmth and competence modulated the general tendency to reduce deceptive behaviour when there was a risk of disclosure compared to when the lying was anonymous, highlighting the importance of these judgements in social evaluation processes. Together, our results demonstrate that the emotional costs and personal moral standards that inhibit engagement in deceptive behaviour are not stable but rather malleable according to the target and the consequences of the deception.